The Role of Self-Compassion on Parenting Stress in Mothers of Early Childhood Children: Systematic Literature Review - Ointu, Renaldi; Hasanati, Nida (Jurnal Indonesia Sosial Sains, 2026)
Background: Self-compassion plays an important role in reducing levels of parenting stress among mothers of young children. Purpose: This systematic review aims to identify the negative relationship between self-compassion and parenting stress, indicating that mothers with higher levels of self-compassion tend to experience lower levels of parenting stress. Method: The PRISMA method was applied through searches of electronic databases, including Google Scholar, APA PsycNET, Springer, and Elsevier. Of the identified articles, 11 journals met the inclusion criteria after undergoing a rigorous selection process. Result: Based on the results of the systematic literature review of various empirical studies, self-compassion plays a significant role in reducing parenting stress among mothers of young children. Early childhood is a developmental phase that requires high levels of attention, emotional involvement, and physical energy from mothers. Conclusion: These conditions often trigger psychological pressure, particularly when mothers face limited personal resources, multiple role demands, and high social expectations regarding motherhood.